Middle East Monitor. East Med - Business Monitor International (London Business Monitor International, 2000)
BMI WP: ​Part of the Middle East Monitor series of newsletters, East Med Monitor provides a source of prime intelligence on Israel, Jordan, Lebanon, Syria and Turkey. It gives you advance warning of key changes in the business environment; regular appraisals of country risk; clear insights into economic and financial trends; and competitive intelligence on company and industry-wide developments and opportunities.
At head of title: MEM Related title: Middle East Monitor. The Gulf Some issues carry a different ISSN 1469-5266 Only few issues of vols 10-17 are available at the library
Keywords: Economic conditions; ECONOMIC CONDITIONS; POLITICAL CONDITIONS; ECONOMIC FORECASTS; MIDDLE EAST; EAST MEDITERRANEAN REGION; PERIODICALS